International Dimensions of Marketing - Russow Lioyd; Terpstra Vern (South-Western Publishing Co, 1999)
This book describes the Marketing Mix from an International Perspective. Marketing and International Marketing, The Environment of International Marketing, Foreign Consumers and Foreign Markets, International Marketing Research, Product Strategies for World Markets, International Distribution Decisions, International Dimensions of Pricing, International Dimensions of Promotion, Listing.